2013
DOI: 10.1124/mol.113.085068
|View full text |Cite
|
Sign up to set email alerts
|

A Re-Evaluation of the Role of hCTR1, the Human High-Affinity Copper Transporter, in Platinum-Drug Entry into Human Cells

Abstract: Cisplatin (cDDP) is an anticancer drug used in a number of malignancies, including testicular, ovarian, cervical, bladder, lung, head, and neck cancers. Its use is limited by the development of resistance, often rationalized via effects on cellular uptake. It has been claimed that human copper transporter 1 (hCTR1), the human high-affinity copper transporter, is the major entry pathway for cDDP and related drugs via a mechanism that mimics copper. This is an unexpected property of hCTR1, a highly selective cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 47 publications
1
65
0
Order By: Relevance
“…However, Holzer et al reported that an enhanced expression of hCTR1 in ovarian cancer cells induced higher accumulation of CDDP and copper but only a marginal increase in the cytotoxicity of CDDP due to improper intracellular localization of CDDP (14). Therefore, the cytotoxicity induced by CTR1 expression and CDDP in cancer cells might still be controversial (28)(29)(30), and this issue should be resolved by performing a further study.…”
Section: Discussionmentioning
confidence: 99%
“…However, Holzer et al reported that an enhanced expression of hCTR1 in ovarian cancer cells induced higher accumulation of CDDP and copper but only a marginal increase in the cytotoxicity of CDDP due to improper intracellular localization of CDDP (14). Therefore, the cytotoxicity induced by CTR1 expression and CDDP in cancer cells might still be controversial (28)(29)(30), and this issue should be resolved by performing a further study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, much work has centred on the importance of copper transporters, such as CTR1, which can mediate uptake of cisplatin by yeast [4,5]. Although some evidence suggests that in human cells CTR1 can take up cisplatin and deliver it in a form that is capable of binding DNA and triggering apoptosis [6], iconoclastic data continue to emerge [7]. Other membrane proteins may also play a role in the uptake of platinum drugs and, in collaboration with the Giacomini laboratory, we showed that cells overexpressing the organic cation transporters OCT1 and OCT2 were significantly more sensitive to oxaliplatin than cisplatin [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, survival with early stage NSCLC is also improved by chemotherapy following surgery (3). Chemotherapy may be administered alone or in combination with surgery or radiation therapy, and platinum-based anti-tumor agents, particularly cisplatin, have been widely used for the treatment of various human cancers, including NSCLC (4,5). These agents are initially effective in lung cancer patients, but due to the development of resistance and relapse in treated patients, the benefit of these platinum based compounds has been limited.…”
Section: Introductionmentioning
confidence: 99%